Chapter 8. The politics of place names: a summation - Wråkberg, Urban (Septentrio Conference Series, 2015)
Remarks at the conclusion of a workshop, sponsored by the U.S. National Science Foundation, and held in Oslo, Norway, from 12-13 May 2015, to discuss the historic place names of the High Arctic archipelago of Franz Josef Land. Discussed are new approaches to toponymic research suggested at the workshop, as well as perspective based in the author’s research on the toponymic history of Kong Karls Land in Svalbard.